دور الاقتصاد المعرفي في تعزيز النمو الاقتصادي في الدول المغاربية (دراسة قياسية للفترة 2011-2021) - خلف, منى; بقاط, حنان (جامعة الوادي - University of Eloued, 2022)
The present study aims to determine the extent to which the knowledge economy contributes to the promotion of the economic growth of the Maghreb countries (Algeria, Morocco, Tunisia) based on the Global Innovation Index 2011-2021, Using the -PMG Panel ARDL model, The study found a long-term correlation between the knowledge economy through the Innovation and Economic Growth Index in the Maghreb countries as the higher the Global Innovation Index by 1% will lead to an increase in the rate of economic growth by 0.22%.
The role of the knowledge economy to promoting economic growth in the Maghreb countries )Econometric study for the period 1144-1114(
مقال
Keywords: اقتصاد معرفي؛ مؤشر الابتكار؛ نمو اقتصادي; Panel ARDL knowledge economy; Innovation Index; economic growth